Distributed situation awareness in road transport : theory, measurement, and application to intersection design /: theory, measurement, and application to intersection design. (2018) - Salmon, Paul M; Read, Gemma J. M; Walker, Guy; Lenné, Michael G; Stanton, Neville A (Neville Anthony), 1960-
No abstract available